Breastfeeding and complementary feeding in premature infants treated by a secondary reference service: a cohort study - Parreiras, Emanuelle Emília Ferreira; Lima, Luciana Moreira; Serafim, Tatiane Cristina; Rocha, Kelvin Oliveira; Martins, Felipe Oliveira; Freitas, Brunnella Alcantara Chagas de (Ciência e Natura, 2022)
Premature infants are vulnerable in the course of feeding practices, with lower rates of breastfeeding and inadequate feeding. To analyze breastfeeding rates, use of cow's milk and dietary inadequacies of premature infants in the second semester of Corrected Gestational Age (CGA), comparing them in two moments. This is a non-concurrent cohort with documentary analysis of medical records of 118 premature infants monitored at a secondary referral health service. Sociodemographic and perinatal data were analyzed in relation to the type of breastfeeding, feeding error and use of cow's milk in two moments: 6 months and 12 months of CGA. A reduction in breastfeeding rates was observed by the second semester of CGA (48.3% vs. 36.4%). The prevalence of dietary inadequacies was significant and showed no differences between the two periods (26.3 vs. 27.1%), but the rates of use of cow's milk increased in the second moment (11% vs. 26.3%). Birth weight less than 2000g was associated with a 4.2 times greater chance of artificial feeding in the first year of CGA. Low rates of breastfeeding, use of cow's milk and inadequate complementary feeding are expressive in premature infants whose families have low education and low income.